Effect of Plasticizer and Concentration on Characteristics of Bioplastic Based on Cellulose Acetate from Kapok (Ceiba pentandra) Fiber - Rahmatullah; Rizka Wulandari Putri; Muhammad Rendana; Untung Waluyo; Tedi Andrianto (Science and Technology Indonesia, 2022)
The synthetic plastics that made from petroleum material have been widely used in all industrial sectors. They cause some serious problems for the environment. There are semi-synthetic plastics or biodegradable plastics which are made from natural polymers such as cellulose to mitigate this problem. Biodegradable plastics can fulfill the needs of society because they can be decomposed easily into the environment. This research used laboratory experimental methods through several processes: kapok fiber isolation, cellulose acetate production and purification, and manufacture of bioplastics. The characteristics of bioplastics was analyzed using some parameters such as density, tensile strength, elongation, Young's modulus, water absorption, biodegradability, compound group analysis using Fouier-Transform Infrared Spectrometer (FTIR) and bioplastic morphology analysis by using Scanning electrone microscopy (SEM). This study aimed to determine the effect of the plasticizer type and concentration on the bioplastics characteristics that was divided into several different concentrations of glycerol and sorbitol plasticizers (20%, 30%, and 40%). The fabrication of composite bioplastics used the cellulose acetat from kapok fiber, starch, and types of plasticizer (glycerol, and sorbitol). The results of the study showed that the addition of different plasticizers, such as glycerol and sorbitol gave distinct effects on the bioplastics product characteristics. The optimum concentration of glycerol addition affected the bioplastic characteristics with the best results were 40% concentration generate density of 0.836 g/mL, tensile strength of 0.818 MPa, water absorption value of 22.23%, and degradation plastic mass about 39.7%. The addition of sorbitol also affected the bioplastic characteristics, where the best results were 40% concentration produced bioplastic density of 0.941 g/mL, percent elongation at 3.94%, young’s modulus of 0.726 MPa, and degradarion mass of 32.05%. The morphology of bioplastic showed the high homogeneity on concentrations of 40% glycerol and 30% sorbitol.